The Effects of Giving Feedback on the Persuasive Writing of Fourth- and Fifth-Grade Students - Philippakos, Zoi A.; MacArthur, Charles A. (Reading research quarterly, 2016)
Peer review is a reciprocal process in which writers both give and receive feedback. Both activities may contribute to student learning; however, few studies have examined the effects of giving feedback separately. The purpose of this study was to examine the effects of giving feedback on the quality of the reviewers' own persuasive writing. Fourth-and fifth-grade students (n = 145) received training in evaluation using genre-specific criteria. They were then randomly assigned to three groups: reviewer, reader control, and time control. The reviewers read persuasive essays, rated them, and gave written suggestions. To control for the effect of reading the essays, the reader control group read the same essays but did not evaluate them; finally, the time control group read narratives to control for time and effort. On the immediate posttests, to assess effects on revision, all students revised two essays written at pretest. To assess transfer and delayed transfer, students wrote and revised essays on new topics. On the immediate posttests, students in the reviewer group included more elements to address the opposing position and end with a message to the reader. In addition, reviewers produced better quality final essays than both control groups did on one immediate posttest and the transfer posttest, and better essays than the reader control group did on the delayed transfer. Implications for research and practice are discussed.